2016
DOI: 10.14687/jhs.v13i3.4209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of internet supported dental education: Initial outcomes in a study sample

Abstract: The aim of this preliminary mixed method study was to understand dental students' thoughts on internet supported learning environment (ISLE) and to investigate its' impact on their academic success. The research was designed to enroll the students from the 7th semester of School of Dentistry. The lecturer taught dental students for four hours (within four weeks) on the topics of "anamnesis, extraoral and intraoral examination". Voluntary twenty-four students participated actively to the ISLE. During the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The success of e-learning adoption is also highly dependent on technological accessibility and having a good Internet connection. 4 , 10 , 15 The dental students from KAUFD who participated in the current study and the dental students from King Saud University, Riyadh, reported high levels of technology accessibility, assuring the presence of a good technological foundation for e-learning adoption in the primary institutions in Saudi Arabia. 3 Participants also reported an acceptable level of online skills and motivation level for using online tools, but they preferred using such tools for personal uses rather than for learning purposes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The success of e-learning adoption is also highly dependent on technological accessibility and having a good Internet connection. 4 , 10 , 15 The dental students from KAUFD who participated in the current study and the dental students from King Saud University, Riyadh, reported high levels of technology accessibility, assuring the presence of a good technological foundation for e-learning adoption in the primary institutions in Saudi Arabia. 3 Participants also reported an acceptable level of online skills and motivation level for using online tools, but they preferred using such tools for personal uses rather than for learning purposes.…”
Section: Discussionmentioning
confidence: 89%
“… 7 9 However, the influence of online learning methods on students’ satisfaction, motivation, and self-assessment is greater when it is integrated with conventional methods. 1 , 10 Students in health profession fields are required to gain and integrate theoretical and clinical knowledge in a suitable environment to become safe and competent health professionals. 11 The importance of one-to-one supervision and hands-on training in such fields poses a challenge for e-learning curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Firat and Bozkurt (2020) also found out statistically significant correlation between the time spent online and online learning readiness. Similarly, many studies concluded that the success of e-learning adoption highly depends on technological accessibility and having a good Internet connection (Al-Asmari and Rabb Khan, 2014;Sarsar, Kaval, Klasser and Guneri, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This method also enables use of time efficiently according to individuals and gives the students opportunity to work at their own pace as well as repeat the program whenever needed. [2] Besides it advantages, various primary drawbacks that come with online learning are student isolation and technical issues. [5] In addition, online learning eliminates real-life communication during the training course, failure to overall clarify the topic.…”
Section: Journal Of Advances In Dental Practice and Researchmentioning
confidence: 99%
“…It is done by various innovative approaches such as problem-based learning (PBL) and case-based learning (CBL). [2] Performance by teacher on patients like as in case of conventional demonstration is a preferred method of practical education. [3] In students, this method has shown to be effective in better perception of clinical procedures, their communication skills, and increases overall self-confidence.…”
mentioning
confidence: 99%